البروكالسيتونين كعلامة تنبؤية وتشخيصية مبكرة للإنتان عند مرضى السرطان - عبد الله نادر; أحمد علاء (Latakia University Journal -Medical Sciences Series, 2017)
أجريت الدراسة لتقييم كفاءة البروكالسيتونين في تشخيص الإنتان الجرثومي عند مرضى السرطان في مركز المعالجة الكيماوية والشعاعية في مشفى تشرين الجامعي باللاذقية في الفترة الواقعة بين 3\1\2015 إلى 28\3\2016. شملت الدراسة (45) مريضاً كان منهم (25) مريض انتان مثبت و(20) مريض انتان غير مثبت، وجميعهم لديهم حمى وغير متناولين للصادات الحيوية حيث خضع المرضى لتقييم بدئي شامل تضمن فحص سريري دقيق وفحوص مخبرية عديدة وصور شعاعية كما تم قياس البروكالسيتونين أثناء الترفع الحروري ومقارنته مع البروتين المتفاعل C، وأشارت النتائج الى وجود ارتباط هام بين البروكالسيتونين والانتان حيث كانت القيم الوسطية للبروكالسيتونين عند مرضى الانتان المثبت 16.9 نغ/مل مقابل 0.7 نغ/مل عند مرضى الانتان غير المثبت، كما ترافق ازدياد تركيز البروكالسيتونين مع زيادة شدة الانتان، واظهرت الدراسة أن البروكالسيتونين أكثر حساسية ونوعية من ال CRP في تشخيص وجود انتان عند مرضى السرطان. The study is carried out to estimate the efficiency of Procalcitonin in the diagnosis of bacterial infection in cancer patients at Chemical and Radiation Therapy Center in Tishreen University Hospital in Lattakia between 3/1/2015-28\3\2016. This study has included 45 patients, 25 with infection and 20 without infection, all of them have a fever and don’t take antibiotics. The all of patients has undergone a comprehensive initial assessment included history, physical examination, biochemical parameters and X-ray images. Procalcitonin was also measured during fever and compared with C-reactive protein CRP, the results indicated that there is a significant correlation between Procalcitonin and infection, where the median values Procalcitonin in patients with infection 16.9 ng/ml compared to 0.7 ng/ml in patients without infection, Procalcitonin concentration was also associated with the severity of the infection, the study showed that the Procalcitonin is more sensitive and specific of the CRP in diagnosing of sepsis in cancer patients.